Neurological disorders, depression and inflammation: is there a common link?. (July 2015) - Halaris, Angelos
To understand the origin of co-morbidity between neurological disorders and depressive illness, a multifactorial model is in order. Diverse approaches have been undertaken to elucidate the co-morbidity. Of these, the concept that inflammatory processes contribute to brain-related pathologies has been gaining traction. Inflammatory processes have been identified in most, if not all, neurological conditions. Similarly, major depressive disorder has been associated with a chronic proinflammatory status. Activation of the immune response can alter neurotransmission leading, among others, to serotonin deficiency, and increased production of neurotoxic substances contributing to primary disease progression. Therefore, inflammatory factors might serve as biomarkers to predict and ultimately prevent the development and progression of neuropsychiatric disorders as well as to identify the most efficacious treatments.